PENGARUH BUDAYA ORGANISASI TERHADAP PENGELOLAAN RASTRA DI DESA BULUCENRANA KECAMATAN PITU RIAWA KABUPATEN SIDENRENG RAPPANG - Elmayanti Elmayanti; Hariyanti Hamid; Monalisa Ibrahim (JIA: Jurnal Ilmiah Administrasi, 2020)
This research provides a purpose to understand culture on prosperous rice management in Bulucenrana Village, Pitu Riawa District, Sidenreng Rappang Regency and to determine the factors that influence organizational culture in Bulucenrana Village, Pitu Riawa District, Sidenreng Rappang Regency. The population of this research was 119 people. A sample of 54 people. The sampling technique used was purposive sampling. This type of research is descriptive quantitative. The data collection techniques used were observation, interview, questionnaire and literature study. The data analysis technique used was descriptive statistics and with the help of the SPSS version 21 application. The results showed that the influence of organizational culture in Bulucenrana village with a percentage of 59.58% was in the unfavorable category. Rastra management in Bulucenrana Village with a percentage of 55.66% is in the poor category. Based on the value of t count> t table or 2.750> 2.006, then H0 is rejected, meaning that the influence of organizational culture has a significant effect on the management of prosperous rice in Bulucenrana Village, Pitu Riawa District, Sidenreng Rappang Regency with a contribution percentage of 57.1%. Factors Affecting Organizational Culture: 1. Organizational history factors 58%, 2. Cultural factors 58.4% and 3. Language factors 54.4%. Based on the explanation above, it can be concluded that factors affecting the Organizational Culture in Bulucenrana Village with a percentage of 56.66% are in the unfavorable category.